Mathematical model and algorithm for calculating the cycles of the cells of the graph map - Ivanov, Boris N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2021)
The selected properties of the cycles of the DFS-basis block of a simple graph map allowed us to create a mathematical model for calculating the cycles of the cells of the graph map. According to this model, a practical algorithm for calculating the cycles of the graph map cells is proposed. The algorithm has a quadratic complexity relative to the number of vertices in the graph.